THE UNITED STATES UNILATERAL WITHDRAWAL FROM THE RESTRICTIONS OF IRAN’S NUCLEAR PROGRAM IN JCPOA 2015 UNDER INTERNATIONAL LAW - Christopher Valerio Jovan (Padjadjaran Journal of International Law, 2020)
Abstract In 2015, Iran with the P5 + 1 countries (China, France, Germany, Russia, Britain and the United States, as well as the European Union High Representative for Foreign Affairs and Security Policy) agreed on a JCPOA (Joint Comprehensive Plan of Action) which deals with Iran's nuclear program. The Joint Comprehensive Plan of Action 2015 (JCPOA) is a controversial agreement. First, the JCPOA's status in international law is debated and is not considered as an international treaty. In the midst of the uncertainty over the status of the JCPOA, on May 8 2018, the United States unilaterally declared that it was withdrawing from the JCPOA. Even though the JCPOA has been endorsed by UN Security Council Resolution 2231 (2015). Thus, other JCPOA participating countries view the withdrawal of the United States as an act that is against international law. This article aims to determine whether the JCPOA is an international treaty and whether the withdrawal of the United States from the JCPOA is justified under international law. Keywords: JCPOA, UN Security Council Resolution, Withdrawal Abstrak Pada tahun 2015, Iran dengan negara-negara P5+1 (China, Prancis, Jerman, Rusia, Inggris dan Amerika Serikat, serta Perwakilan Tinggi Uni Eropa untuk Urusan Luar Negeri dan Kebijakan Keamanan) menyepakati JCPOA (Joint Comprehensive Plan of Action) mengenai pembatasan program nuklir Iran. Joint Comprehensive Plan of Action 2015 (JCPOA) merupakan perjanjian yang mengundang kontroversi. Pertama, status JCPOA mendapat perdebatan karena dianggap bukan perjanjian internasional. Kemudian pada 8 Mei 2018, Amerika Serikat secara sepihak menyatakan menarik diri dari JCPOA. Padahal JCPOA telah dimasukkan ke dalam Resolusi Dewan Keamanan PBB 2231 (2015). Sehingga peserta JCPOA lainnya menganggap tindakan Amerika Serikat sebagai perbuatan yang bertentangan dengan hukum internasional. Artikel ini bertujuan untuk mengetahui apakah JCPOA merupakan suatu perjanjian internasional dan apakah penarikan diri Amerika Serikat dari JCPOA dapat dibenarkan berdasarkan hukum internasional. Kata kunci: JCPOA, Penarikan Diri, Resolusi Dewan Keamanan PBB